2014
DOI: 10.4236/me.2014.53023
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Quality and Inflation

Abstract: The purpose of this paper is to empirically analyze the effects of the quality of institutions on inflation. Using panel data from 1991 to 2007, we find that increase in institutional development which is measured by the ratio of domestic credit to private sector to GDP has significant and sizeable effect on inflation. This paper finds that in countries with high inflation rates, financial sectors cannot resist current levels of inflation and banking system does not decrease inflation in the environment where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In developing countries, several empirical studies (Cukierman et al, 1992;Hielscher & Markwardt, 2012;Klomp & de Haan, 2010) did not find a negative relationship between central bank independence and inflation rates. Other research shows that there is a negative relationship between central bank independence and inflation in certain conditions, for example, improvement in institutional quality (Agoba et al, 2017;Bouoiyour & Selmi, 2013;Hove et al, 2017;Salahodjaev & Chepel, 2014). Other studies have found a negative relationship between the independence of central banks in developing countries (Andriani & Gai, 2013;Garriga & Rodriguez, 2019;Nagac & Rizvanoghlu, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In developing countries, several empirical studies (Cukierman et al, 1992;Hielscher & Markwardt, 2012;Klomp & de Haan, 2010) did not find a negative relationship between central bank independence and inflation rates. Other research shows that there is a negative relationship between central bank independence and inflation in certain conditions, for example, improvement in institutional quality (Agoba et al, 2017;Bouoiyour & Selmi, 2013;Hove et al, 2017;Salahodjaev & Chepel, 2014). Other studies have found a negative relationship between the independence of central banks in developing countries (Andriani & Gai, 2013;Garriga & Rodriguez, 2019;Nagac & Rizvanoghlu, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, empirical research shows that politically unstable countries have higher inflation rates (Salahodjaev & Chepel, 2014;Khan & Hanif, 2018).…”
Section: Introductionmentioning
confidence: 99%